Non-Native Speakers’ Perception and Motivation for Learning English Language through Movies - Miftahul Jannah, Awg Baderulhisam; Norehan, Zulkiply (SecholianPublication, 2023)
The global dominance of the English language has motivated individuals whose first language is not English to actively pursue fluency in English. For non-native speakers of English, acquiring the language is an intricate journey that demands substantial time and effort, accompanied by a range of challenges. In recent years, English movies have emerged as captivating tools for language learning, effectively aiding in enhancing vocabulary and essential language skills. These insights stem from past research that studied how non-native speakers learn English through movies. However, despite the valuable findings from these studies, there remains a discernible gap in our understanding of this field. In addressing this gap, the current study intended to investigate the perception and motivation of non-native speakers in learning English through movies. The study collected data by conducting surveys among non-native English speakers who were undergraduate students at a local public university. The findings revealed that these non-native speakers favour using movies as a method for learning English as a second language, and this medium enhances their motivation to learn. Building upon the existing foundation of research, this study significantly contributes to the body of knowledge by addressing the substantial research gap that exists in comprehending non-native speakers' perspectives on learning the English language through the medium of movies.